Long-term results of open surgical repair of rotator cuff tears [Rotator kilif yirtiklarinda açik cerrahi onarimin uzun dönem sonuçlari.] - (:unkn) unknown (My University, 2004)
OBJECTIVES: We evaluated the long-term results of rotator cuff tears treated by open surgical repair. METHODS: Ninety shoulders of 88 patients (36 females, 52 males; mean age 57 years; range 36 to 75 years) with rotator cuff tears were treated by open surgical repair and acromioplasty. A three-staged rehabilitation program was implemented following surgery. Objective evaluations were made with the use of the Constant-Murley scoring system. Pain was assessed through a visual analog scale. The mean follow-up period was 61 months (range 24 to 102 months). RESULTS: The mean Constant-Murley score increased from preoperative 41.7 (range 12 to 82) to postoperative 79.7 (range 42 to 100) (p<0.0001). The mean preoperative and postoperative pain scores were 7.5 (range 4 to 10) and 1.25 (range 0 to 5), respectively (p<0.0001). Only eight patients (9%) showed dissatisfaction with the surgical outcome. The remaining 80 patients (91%) were satisfied with the outcome and returned to their previous night comfort and daily activities. None of the patients had postoperative nerve palsy or limitations in shoulder functions. Two patients (2.2%) developed superficial soft tissue infections that disappeared following multiple wound debridements. CONCLUSION: Our long-term results favor open surgical repair and acromioplasty in the treatment of patients with rotator cuff tears.